The Relationship between Human and Nature from the Perspective of Instrumental Rational Thought - Zhang, Taijin (Journal of Theory and Practice of Social Science, 2023)
The relationship between man and nature has been in a very dangerous state, which forces us to re-examine the relationship between man and nature. Horkheimer's instrumental rationality thought deeply criticized human's blind worship of the utility of science and technology. The proliferation of instrumental rationality concept not only makes human ignore their own value, but also leads to a crisis in the relationship between human and nature.